Inteligência emocional no ambiente organizacional - VEIGA, Aline Cristine Ramos; VALÉRIO, Welisson Campos (109, 2022)
A inteligência emocional é uma competência que deve ser observada com maior atenção no mercado de trabalho, pois, o nível de estresse diário se torna cada vez mais presente e notório entre as pessoas. É importante que gestores e colaboradores entendam que a inteligência emocional pode interferir e influenciar de maneira positiva ou negativa em suas tarefas, e consequentemente nos resultados organizacionais. O presente trabalho tem como objetivo apresentar a Inteligência Emocional dentro do ambiente organizacional. Para isto, desenvolveu-se a uma pesquisa relatando do referido assunto, com o intuito de que líderes e gestores das empresas apliquem seus conceitos perante suas equipes de colaboradores. As metodologias utilizadas para a elaboração deste trabalho foram pesquisas bibliográficas em livros e materiais pertinentes ao tema, e uma pesquisa quantitativa, que apontou a relevância de ser utilizado nas empresas. Em seguida, foi desenvolvido o processo de criação do manual. O resultado foi satisfatório atingindo os requisitos exigidos, visando à necessidade do tema abordado a gestão de pessoas

Emotional inteligence is a competence that must be observed with greater attention in the job market, as the level of daily stress becomes increasingly present and notorious among people. It is important that managers and employees understand that emotional intelligence can interfere and influence positively or negatively in their tasks, and consequently in organizational results. This work aims to present Emotional intelligence within the organizational environment. To this end, the production of a manual dealing with this subject was developed, with the intention that leaders and managers of companies apply their concepts to their teams of employees. Aiming at the precepts of environmental and sustainable responsibility, all material was designed on a digital platform and made available on an electronic address created for its dissemination. The methodologies used for the elaboration of this work were, bibliographic searches in books and materials pertinente to the theme, and a quantitative research, which pointed out the relevance of the product to be used in companies. Then, the manual creation process was developed. The result was satisfactory reaching the required requirements, with the creation of a product accessible to the target audience, being a sustainable project and a tool used for people management
Emotional intelligence in the organizational environment
Keywords: Inteligência emocional; Ambiente organizacional; Conflito; Gestão e Negócios